2022
DOI: 10.1155/2022/4114178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Data Augmentation with the BNNSMOTE Algorithm in Seizure Detection Using 1D-MobileNet

Abstract: Automatic seizure detection technology has important implications for reducing the workload of neurologists for epilepsy diagnosis and treatment. Due to the unpredictable nature of seizures, the imbalanced classification of seizure and nonseizure data continues to be challenging. In this work, we first propose a novel algorithm named the borderline nearest neighbor synthetic minority oversampling technique (BNNSMOTE) to address the imbalanced classification problem and improve seizure detection performance. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…The model has achieved 13% improvement in age prediction due to augmented data which enables better capture of age-related patterns and factors. The authors of [16] suggested BNNSMOTE (Borderline Nearest Neighbour Synthetic Minority Oversampling Technique) for imbalanced seizure dataset and improved the seizure detection. BNNSMOTE generates synthetic seizure samples from borderline instances near the decision boundary.…”
Section: Related Workmentioning
confidence: 99%
“…The model has achieved 13% improvement in age prediction due to augmented data which enables better capture of age-related patterns and factors. The authors of [16] suggested BNNSMOTE (Borderline Nearest Neighbour Synthetic Minority Oversampling Technique) for imbalanced seizure dataset and improved the seizure detection. BNNSMOTE generates synthetic seizure samples from borderline instances near the decision boundary.…”
Section: Related Workmentioning
confidence: 99%